Treatment patterns and clinical outcomes in patients with rheumatoid arthritis initiating etanercept, adalimumab, or Janus kinase inhibitor as first-line therapy: results from the real-world CorEvitas RA Registry - Dimitrios A. Pappas; Jacqueline O’Brien; Lin Guo; Ying Shan; Joshua F. Baker; Gregory Kricorian; Scott Stryker; David H. Collier (Arthritis Research & Therapy, 2023)
Abstract Background Real-world studies assessing the comparative effectiveness of biologic or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) as first-line targeted therapy are scarce. We analyzed the real-world persistence and effectiveness of etanercept (ETN), adalimumab (ADA), and Janus kinase inhibitors (JAKis) as first-line therapy in b/tsDMARD-naïve patients with rheumatoid arthritis (RA). Methods Adults (≥ 18 years) enrolled in the CorEvitas RA Registry and initiating ETN, ADA, or a JAKi (alone or in combination with csDMARDs) between November 2012 and June 2021 were included if they had 6 and/or 12 months’ follow-up. Treatment persistence and effectiveness outcomes including the change in Clinical Disease Activity Index (CDAI) and patient-reported outcomes (PROs) were evaluated at follow-up, adjusting for covariates using linear and logistic regression models. An exploratory analysis for patients on monotherapy was also conducted. Results Of 1059 ETN, 1327 ADA, and 581 JAKi initiators; 803 ETN, 984 ADA, and 361 JAKi initiators had 6 months’ follow-up. JAKi initiators were older and had a relatively longer disease duration than ETN or ADA initiators (mean age: 61.3 vs 54.5 and 55.5 years; mean duration of RA: 8.1 vs 5.7 and 5.6 years). Unadjusted mean improvements in CDAI and PROs were similar between the groups at 6 months, except the proportion achieving LDA, remission, and MCID in CDAI, which were numerically higher in the ETN and ADA groups vs JAKi group (LDA: 43.4% and 41.9% vs 32.5%; remission: 18.2% and 15.1% vs 11.5%; MCID: 46.5% and 47.8% vs 38.0%). Adjusted effectiveness results did not reveal statistically significant differences between treatment groups at 6 months, with an exception in MCID (odds ratio [95% CI] for JAKi vs ETN: 0.65 [0.43–0.98]). At 6 months, 68.2% of ETN, 68.5% of ADA, and 66.5% of JAKi initiators remained on therapy. The findings at 12 months’ follow-up and sensitivity analysis among monotherapy initiators also showed no differences in effectiveness outcomes between the groups. Conclusions This analysis of real-world data from the CorEvitas RA Registry did not show differences in clinical effectiveness and treatment persistence rates in b/tsDMARD-naïve patients initiating ETN, ADA, or JAKi as first-line targeted therapy either alone or in combination with csDMARDs.